Prevalence and risk factors of type 2 diabetes in the adults in haikou city, hainan island, china. - Zhenfang Xia; Zhuansuo Wang; Qunfang Cai; Jianjun Yang; Xuan Zhang; Tubao Yang (Tehran University of Medical Sciences, 2013)
Type 2 diabetes mellitus (T2DM) occurs around the world with high prevalence and causes serious physical harm and economic burden to the afflicted. Haikou City is China's southernmost tropical island city, which has not been previously studied for its T2DM prevalence. The objective of the study in employing a cross-sectional survey is to discuss the epidemiologic status of T2DM in Haikou City and to analyze the possible determinants.A total of 12,000 community residents over 18 years old from four districts in Haikou City were stratified-randomly sampled. A questionnaire survey and physical examination were conducted. Data entry and statistical analysis were performed using SPSS17.0 software.The prevalence of T2DM in Haikou City was 5.3% (5.15% for males and 5.46% for females). According to the multivariate analysis, the positive factors mainly associated with T2DM in the city included family history, Waist-to-Hip Ratio (WHR), triglycerides, low high-density lipoproteins (HDL), and blood pressure. For both men and women, family history was the highest independent risk factor associated with T2DM (OR= 47.128). The T2DM risk increased with increasing metabolic aggregate.The prevalence of T2DM for the community population of Haikou City was low. The possible risk factors included age, occupation, BMI, waist circumference, WHR, overweight, systemic obesity, central obesity, systolic blood pressure, diastolic blood pressure, total cholesterol, triglycerides, low-density lipoproteins, family history, and HDL.